AN ANALYSIS OF AIRBNB USER EXPERIENCE IN INDONESIA - Najwa Pramesti, Anggit
This study investigates the experiences of Airbnb users staying in three Southeast Asian nations, focusing on their major cities. Delving into the context of Indonesia, a country that experienced a delayed entry into the Airbnb market yet has emerged as a rapidly growing player in Southeast Asia's inbound travel, particularly in Bali and Jakarta. The latter, Indonesia's bustling capital city, witnessed a significant uptick in tourist arrivals and a concurrent surge in Airbnb utilisation and listings. However, scant research exists concerning the factors influencing user experiences in Jakarta and the encountered challenges. Moreover, cross-country comparative analyses involving Thailand and Malaysia stand to reveal shared and culturally distinct elements shaping consumer satisfaction. Thailand, a perennial tourist magnet, and Malaysia, a nation endowed with cultural heritage and scenic beauty, are both witnessing a growing Airbnb presence. The aim is to identify the elements that influence the user experience of Airbnb in Jakarta, Indonesia, and the problems users encounter during their stay. By exploring these factors, the research seeks to determine if strengthening them can help Airbnb hosts increase their earnings. Additionally, the study analyses Airbnb's performance in various nations to gain insights into its functioning in Indonesia. The research methodology is exploratory and employs qualitative techniques, specifically netnography, to analyse online consumer culture and reviews on the Airbnb website. The results reveal that the quality and attributes of the lodging, referred to as the "place," emerged as a critical factor in all three cities. Factors such as cleanliness, comfort, location, facilities, and Wi-Fi were highly valued by users, leading to overall satisfaction. The involvement and support provided by hosts were also identified as significant contributors to the user experience. The study emphasises the importance of these variables in shaping the customer experience of Airbnb in Jakarta, Indonesia, and provides insights for improving the service and enhancing host earnings. The findings contribute to a better understanding of Airbnb's performance in Southeast Asia and offer valuable insights for the company's operations in Indonesia based on successful practices from other countries.